RECENT DEVELOPMENTS IN SYNTHETIC METHODS AND PHARMACOLOGICAL ACTIVITIES OF QUINAZOLINONE DERIVATIVES: A REVIEW - Meftah, Omar N.; Ali, Ahshan; Ali G. Al-kaf (Universal Journal of Pharmaceutical Research, 2025)
This review article offers A brief overview of the most current advancements in synthesis methods and with regard to the pharmacological effects of quinazolinone derivatives. A heterocyclic hybrid quinazolinone having the chemical formula C8H6N2O. It is composed of rings that have been fused together i.e benzene and pyrimidine. The production of quinazolinone derivatives can be accomplished using a variety of methods, such as the Aza-diels-alder reaction, Aza-witting reaction, reaction aided by microwaves, metal-mediated synthesis, palladium-catalyzed reaction, copper-catalyzed reaction, ultrasound-promoted reaction, oxidative cyclization, reagent refluxing, one-pot synthesis, and aqueous media. This review paper included a wide spectrum of pharmacological activities, including a wide range of antibacterial, anti-inflammatory, and analgesic properties of quinazolinone derivatives as well as anti-cancer and anti-oxidant properties were covered in this study. Peer Review History: Received 15 October 2024; Reviewed 7 November; Accepted 21 December; Available online 15 January 2025 Academic Editor: Dr. Iman Muhammad Higazy , National Research Center, Egypt, imane.higazy@hotmail.com Reviewers: Dr. Sameh Abdelmoneem Mohammed Ali, Faculty of Pharmacy, Beni-Suef University, Egypt, same7_pharma18@yahoo.com Dr. Sally A. El-Zahaby, Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, King Salman International University, Egypt, sally.elzahaby@yahoo.com